EFFECTS OF GUIDED DISCOVERY, SIMULATION AND EXPOSITORY STRATEGIES ON SECONDARY SCHOOL STUDENTS’ IMMEDIATE AND DELAYED RECALL IN GEOGRAPHY IN EDO STATE (2015)
Geography is one of the subjects that is relevant to life experiences. Geography by its nature requires both operational and conceptual understanding of its content for students to acquire geographical skills. Findings from previous studies on teaching and students’ performances in geography have shown that the traditional teaching strategies which are prevalent in Nigerian classrooms are less effective .Teaching strategies which can apply the new knowledge and develop student’s skill are desirable. Therefore, this study investigated the effect of instructional strategy (guided discovery, simulation and expository strategies) on secondary school students’ immediate and delayed recall in Geography ,with study habit as moderator variable. The study adopted the quasi-experimental design. Study habits was studied as moderator variable. A 3x2 factorial design with pretest-posttest, non-randomized control group was employed. A multi-stage sampling technique was used to select the Edo central senatorial district out of the three senatorial districts in the state where there is high concentration of co- educational schools. Two co- educational schools were randomly selected from each of the three selected Local Government Areas (Esan West, Esan Central & Esan Southeast ) in the Edo central senatorial district. Participants were 480 senior secondary two students in non- randomized intact classes.Geography Achievement Test (r=0.80), and Study Habit inventory (r = 0.81) were used. Data were analysed using analysis of covariance and scheffe test as post-hoc at 05 significant level There was significant mean effect of treatment (Guided discovery (F (2, 469) = 59.369, 2 = 0.200) and Simulation (F(2, 467) = 41.000 2 = 0.148) on student immediate and delayed recall (24 hours later) in Geography. Significant difference existed among participants exposed to guided discovery (x ̅ = 16.501), simulation (x ̅ = 14.550) and expository (x ̅= 12.959). With regards to delayed recall, guided discovery (x ̅ = 18.370), was more effective than simulation (x ̅ = 16.921), while expository was the least (x ̅ = 12.954). The mean score shows that students profited most from guided discovery followed by simulation, while students exposed to expository teaching recorded the least in immediate recall in Gepography. Guided discovery (x ̅=18.370) was more effective than simulation (x ̅=16.921), while expository has the least effect (x ̅= 12.951) on delayed recall so students exposed to guided discovery strategy performed significantly better than those exposed to simulation strategy, while those exposed to expository strategy recorded the least score. There was significant main effect of study habit on students’ immediate and delayed recall in Geography . The interaction effect of study habit was not significant. Guided discovery learning strategy was most effective in bringing about improvement in students’ performance in Geography.If this learning strategy is employed in schools, and students are motivated and encouraged, there is the tendency for the teaching and learning of Geography in secondary schools to motivate the learners to choose career that has to do with geography.